A Study on Measuring the Development Level of New Quality Productivity in Chinese Provinces Based on Comprehensive Evaluation and Regression Modeling - Yin, Yitao; Li, Youchen (Transactions on Economics, Business and Management Research, 2024)
With the impetus of globalization and scientific and technological progress, new quality productivity has attracted much attention as a key indicator of regional economic competitiveness and sustainable development. This paper analyzes the panel data of Chinese provinces, municipalities and autonomous regions from 2010 to 2019, and explores the development level of new quality productivity and its relationship with scientific and technological innovation, green development and labor mobility. First, the entropy method was used to calculate the information entropy value, information utility value and weight coefficient of each indicator to reveal the importance and contribution of different indicators in regional development. The results of the study show that Guangdong, Jiangsu and Zhejiang are outstanding in terms of new quality productivity, especially in the high-tech industry and environmental protection, where the investment and achievements are remarkable; in contrast, Gansu, Inner Mongolia, Heilongjiang and other provinces are facing greater development challenges and need to increase scientific and technological innovation and environmental protection. Second, the impact of labor mobility on NQP is analyzed by constructing a linear regression model, and it is found that the two show a significant positive correlation, indicating that the improvement of NQP level promotes the enhancement of regional attractiveness to labor. These research results not only provide empirical evidence for local governments to formulate regional economic policies, but also provide important references and strategic suggestions for promoting China's economy towards high-quality development.